Panoramic and periapical radiographs utilization in Disaster Victim Identification (DVI): narrative review - Vivin Nadine Ekayultania; Ryna Dwi Yanuaryska; Silviana Farrah Diba (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The purpose of this narrative review is to discover radiographic images in panoramic and periapical radiographs that are used as identifiers and to compare the use of panoramic and periapical radiographs in identification based on DVI. Review: The databases used in this narrative review are Google Scholar, PubMed, and Science Direct. A total of 1258 search results appeared based on keywords. The search results were selected by title and abstract according to their relevance to the review topic, then results are selected again based on the inclusion and exclusion criteria. Total of 38 literatures were reviewed. This review shows radiographic identifiers used in panoramic radiographs are tooth restorations, crown, Root Canal Treatment (RCT), dental bridge, dental implants, maxillary sinus, rectilinear metal plate, orthodontic brackets, tooth anomaly, and root morphology. The radiographic identifiers used in periapical radiograph are tooth restorations, PSA, tooth anomaly, and root morphology. In this review, 53.8% of the literatures used panoramic radiograph for identification, whereas 46.2% used periapical radiograph. Conclusion: This review concluded that the most used radiographic identifier in panoramic radiograph is tooth restoration (57,1%) whereas in periapical radiograph is RCT (83,3%). Panoramic radiography were used in 53,8% of the literatures in this review, it was used more than periapical radiography.